2007
DOI: 10.1007/s00737-007-0177-9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of shame and attribution style in developing PTSD among Japanese University women with negative sexual experiences

Abstract: The roles of shame and attribution style in developing posttraumatic stress disorder (PTSD) were examined among 172 Japanese university women with negative sexual experiences (NSEs) using a structural equation model. "Shame" directly predicted PTSD, whereas "Internal Attribution" and "External Attribution" did not. The effect of Internal Attribution on PTSD was mediated by Shame. In a simultaneous analysis of multi-groups, only the relationship with the perpetrator showed a different contribution for shame in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Both women and men were well represented. Representation of racial and ethnic minorities, however, was sparse and relegated to cross-cultural validation studies [29,30] or refugees [31]. Most employed a retrospective, cross-sectional design with thirteen studies reporting on longitudinal data [30,32,33,34,35,36,37,38,39,40,41,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Both women and men were well represented. Representation of racial and ethnic minorities, however, was sparse and relegated to cross-cultural validation studies [29,30] or refugees [31]. Most employed a retrospective, cross-sectional design with thirteen studies reporting on longitudinal data [30,32,33,34,35,36,37,38,39,40,41,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…This makes victimisation from chikan less traumatic than other 'more serious' sexual crimes such as rape. It is far less likely to result in post-traumatic stress disorder (PTSD) than other negative sexual experiences (Uji et al 2007). Another study shows that chikan victimisation is not essential for the development of an eating disorder, while it is more likely to be the case for other sex crimes (Nagata et al 1999).…”
Section: Cultural Selection Of a Chikan Risk And Women-only Train Carmentioning
confidence: 98%
“…Shame and guilt are also hypothesized as factors associated with PTSD symptom in victims of sexual violence (Feiring et al, 1996;Uji et al, 2007). Previous studies on neurocognitive functioning in combat veterans with PTSD showed identifiable impairments in attention, learning, memory, and executive functioning (Beckham et al, 1998;Vasterling et al, 2002).…”
Section: Introductionmentioning
confidence: 97%